Cartografia estudantil no Colégio de Aplicação da Universidade Federal de Sergipe (1969-1981) - Almeida, Sayonara do Espirito Santo (2021)
This thesis analyzes the student profile of the Colégio de Aplicação of the Universidade Federal de Sergipe. The initial mark, 1969, corresponds to the moment when the college was federalized, and the final mark, 1981, to the year when the Colégio de Aplicação and other units of the university were transferred to the University Campus in the city of São Cristóvão (SE). This transfer of location triggered significant changes for the institution and its subjects. Since this is a work of historical nature, the main methodological procedure was the documentary analysis anchored in the assumptions of the New Cultural History and in the concepts of school records, by Zaia (2011) and Cultural Capital, by Bourdieu (1999). In order to achieve the intended objective, it was used as a basic source: the student dossiers (set of loose sheets composed by birth certificate, enrollment and individual records, course completion certificates, transfer requests and school records), examined in a serial way. Other sources subsidized the research: school regulations, interviews with former students, legislation, general admission exam minutes, ordinances and reports. The documentation survey was carried out at the Centro de Pesquisa, Documentação e Memória do Colégio de Aplicação (CEMDAP) and at the Digital Library of the Federal Senate. The thesis defended is that the configuration of the student profile, coming from distinct social groups, in the UFS' Colégio de Aplicação was a characteristic of the 1969-1981 period, motivated by federalization, by the changes in educational legislation, by the redefinitions of the College's purpose and by the changes in the institution's entrance forms. During this period, the high school faced the changes from Law no. 4.024, of December 20, 1961 to Law no. 5.692, of August 11, 1971, which reflected on the school records of the Application School of UFS, on its administrative and pedagogical organization and on the student career (school curriculum, permanence time and pedagogical activities) of those who entered the institution. The research revealed, among other points, a student body composed of 58% women and 42% men. With a predominance of white (78%) and majority from Sergipe (78%), but also with students coming from other Brazilian states. Being 83% from Aracaju and neighboring towns. These students entered the 5th grade (entrance grade at the Colégio de Aplicação da UFS, which offered the last 4 grades of the 1st grade and the 3 grades of the 2nd grade) through different types of selection: from 1969 to 1971 through admission exams, from 1972 to 1973 through the selection of knowledge tests, as in the admission exams, and from 1974 to 1981 through public lottery among the 1st and 2nd places classified in the 4th grade. The research also showed that, even with 64% of the students coming from private schools located, generally, close to their homes in neighborhoods with a high average salary income, the student profile after the federalization led to a student group also coming from public schools and from more distant neighborhoods, where a population whose average salary income was lower was concentrated.